PENDEKATAN ILMU HAYATI MELALUI MUSIKAL - Rachmi, Anne Fadilla; Satriyo, Stephani Fitria Winda; Ramyacitta, Kanya; Prayunita, Dinda; Khairunissa, Miranti Fitri (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
Nowadays, depletion of food source, disease outbreak, and alternative energy occur as global challenges. With little public awareness, life science actually has answers for the core problem and the solution. Therefore, there should be easy and attractive ways to alter publicâs view and add their knowledge about life science. Indonesian culture is accustomed with oral tradition so musical could be an alternative method for reaching out public awareness. Songs about life science has been previously made and for PKM KC, booklet and video were made for making the songs easier to be understood and were put on web so people can access our works. Our works were made with Adobe Illustrator, Adobe After Effect, Adobe Dreamweaver, and iMovie software. Publication was held through school and radio roadshow and publicâs response was observed. To date, we havenât found any works with life science content that has comprehensive variety except our works. Students and public enjoy our works with accepted message about life science. Musical approach of life science is potential for raising public awareness of the importance of life scienceÂ Keyword: life science, musical, public awareness, learning methode